The Essence and Scope of Medical Units in The Works of Folklore (Journal of Pedagogical Inventions and Practices, 2023)
The role of medical units in folk language and folklore works, their different encounters in dialects, their ethnolinguistic and ethno-folkloristic foundations, the determination of the features of linguo-cultural and linguopoetic expression in linguo-folkloristic and folklore texts are among the urgent tasks awaiting a solution. The solution of these tasks is noteworthy in that it allows to clarify the specific features of the lexicology of the folklore language. In world linguistics, the national language has always been considered as the main internal source that enriches the literary language. The article describes the study of medical units in folklore, the opinion of scientists